An original design for a traveliing crane with pneumatic hoist - Butterfield, Joseph Abbott (My University, 1899)
Introduction: The following drawings, formulae, figures and specifications are for a traveling crane designed especially for the foundry in the K.S.A.C. It is to raise the load six ft. and the maximum load is to be two tons. It is to travel on a bridge made of two channel beams; these beams will be specified in a later drawing. This is a special design because it is designed to secure the most possible head room where but very little was available, and at the same time as little length wise space as possible was to be used. The Differential Chain Hoist is to be attached to lift small loads that would be cumbersome to handle fro the ground and are too small to us e the pneumatic hoist. There is no hard and fast rule that the specifications must be adhered to, because many of the rules and formulae by which they were obtained were only close approximations. It not being possible to secure exact data. First will be the Cylinder This is to be 40” long inside to inside of heads. The thickness of the cylinder walls is taken from Thurston’s Locomotive Cylinder”. Formula T+D p a+b. T+ thickness D=dia of piston +12” a= .0004 to .0005 b = 0 to ½”
Citation: Butterfield, Joseph Abbott. An original design for a traveliing crane with pneumatic hoist. Senior thesis, Kansas State Agricultural College, 1898.
Morse Department of Special Collections
Keywords: Specifications for Piston Rod; Cylinder Head Bolts; Piston Rings; Theses; Manuscripts (documents)